1988
DOI: 10.1007/bf02513251
|View full text |Cite
|
Sign up to set email alerts
|

Life table studies of the walnut leaf beetle, Gastrolina depressa (Coleoptera: Chrysomelidae), with special attention to aggregation

Abstract: SummaryIn order to make clear the relationship between the mortality processes and aggregation on the walnut leaf beetle, Gastrolina depressa, life tables of individual colonies were developed and the major mortality factor and the mode of its action were investigated. Furthermore, the influences of the larval colony size on the survival rate and the developmental period were also investigated in the laboratory.In the laboratory, when the larvae were reared on suitable (soft) host plants, the larger the group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Third, based on this information it can be concluded that emerging D. v. virgifera adults found nearly unlimited food resources on the maize plants. Fourth, aggregation, as a beneficial factor in survival (Chang and Morimoto 1988), has never been reported from larvae, pupae or adults of D. v. virgifera . Finally, it can be concluded for this study that the mortality and survival in each age interval of D. v. virgifera appears to be the result of abiotic factors, such as climate and/or soil conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, based on this information it can be concluded that emerging D. v. virgifera adults found nearly unlimited food resources on the maize plants. Fourth, aggregation, as a beneficial factor in survival (Chang and Morimoto 1988), has never been reported from larvae, pupae or adults of D. v. virgifera . Finally, it can be concluded for this study that the mortality and survival in each age interval of D. v. virgifera appears to be the result of abiotic factors, such as climate and/or soil conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chiang (1965) reported from Diabrotica balteata LeConte that winter mortality can vary from 10 to 20% in 1 year and up to 30–40% in another year depending on climate. The impact of unfertilized eggs on mortality is unknown for D. v. virgifera but is expected to be low based on comparisons made with related beetle species, such as the chrysomelid Gastrolina depressa Baly, where only 0.9 to 2.7% of eggs were unfertile (Chang and Morimoto 1988). The higher egg mortality in pre‐ diapausing and diapausing eggs of D. v. virgifera in 2000/2001 compared with 2001/2002 in this study is likely to be a result of the unusually warm and dry autumn of 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of host use due to feeding facilitation, on the other hand, remains a viable hypothesis. Feeding facilitation (or 'social stimulation') may have occurred via increased stimulation to feed, as has been demonstrated for several species (Wade & Breden, 1986;Chang & Morimoto, 1988;Clark & Faeth, 1997;Nahrung et al, 2001). However, feeding facilitation typically benefits early instars (Reader & Hochuli, 2003;Inouye & Johnson, 2005), resulting in increased larval survivorship or faster development (Lawrence, 1990;Nahrung et al, 2001;Fordyce, 2003;Weed, 2010), which we did not consistently observe.…”
Section: Figurementioning
confidence: 49%
“…Because experiments were conducted under laboratory conditions, we can exclude mechanisms related to protection from natural enemies (Breden & Wade, 1987), thermoregulation (Bryant et al, 2000) and host location efficiency (Weed, 2010). Feeding facilitation (or 'social stimulation') may have occurred via increased stimulation to feed, as has been demonstrated for several species (Wade & Breden, 1986;Chang & Morimoto, 1988;Clark & Faeth, 1997;Nahrung et al, 2001). Improvement of host use due to feeding facilitation, on the other hand, remains a viable hypothesis.…”
Section: Figmentioning
confidence: 99%
“…Increases in group size increase the survivorship of individual larvae, although large differences are only apparent when low numbers are present in aggregations, and the change in aggregation size from 100 to 50 seen on male killing is unlikely to have any significant effect. The mortality of early instar larvae in wild populations is low, and is largely attributable to predation, parasitism and disease (Chang & Morimoto, 1988). It is unknown whether G. depressa, like many other chrysomelids, shows egg cannibalism.…”
Section: Simmmondsmentioning
confidence: 99%